Systematic Analysis of Genes Related to Selenium Bioaccumulation in Microalgae: A Review - Brenda S. Hoyos; Fabian Hernandez-Tenorio; Alejandra M. Miranda; Diego F. Villanueva-Mejía; Alex A. Sáez (Biology, 2023)
Se is one of the essential nutrients for human health and animal growth; it participates in various physiological functions, such as antioxidant and immune response and metabolism. Se deficiency is related in the animal industry to poor production performance and the appearance of health problems in humans. Therefore, interest has arisen in producing fortified foods, nutritional supplements, and animal feed products enriched with Se. A sustainable strategy for bio-based products enriched with Se is microalgae. These are characterized by the ability to bioaccumulate inorganic Se and metabolize it into organic Se for product formulations of industrial interest. Although there are some reports on Se bioaccumulation, further exploration is needed to understand the effects of Se bioaccumulation in microalgae. Therefore, this article presents a systematic review of the genes or groups of genes that trigger biological responses associated with the metabolization of Se in microalgae. A total of 54,541 genes related to Se metabolization distributed in 160 different classes were found. Similarly, trends were identified through bibliometric networks on strains of greatest interest, bioproducts, and scientific production.